Prevalência de constipação intestinal e fatores associados aos seis meses de idade - Carvalho, Flávia Lima de (2016)
Intestinal constipation is the most common intestinal motility disorder in the world. The objective of the current study was to evaluate the prevalence, associated factors and reliability of data on intestinal constipation in children at six months of age, according to the maternal impression; Having as main products two articles: "Intestinal constipation in children at six months of age, according to maternal report of arrested gut" and "Prevalence and factors associated with intestinal constipation at six months of age". This was a cross-sectional analysis of a cohort of live births, who followed mother-infant pairs through monthly home visits in the first six months of life. The power of the current study was 91.36%. The dependent variable was constipation of the child reported according to the maternal impression. The other variables were related to the maternal, infant and eating habits of the child. The database was entered in the statistical software SPSS (Statistical Package for the Social Sciences) version 10.0, later validated in the statistical software EPIDATA and analyzed with the help of the program STATA, version 12.0. Pearson's chi-square test was used, and their respective 95% confidence intervals (95% CI). The multivariate analysis was performed using Poisson regression in a hierarchical analysis model, adopting the significance level of 20% (p <0.20), and maintaining in the final model the variables that showed association with the dependent variable At the level of statistical significance p <0.05. To evaluate the concordance between the maternal impression and the characteristics of the intestinal habit, the kappa index was used. Among the 1,134 infants studied, 12.3% of the population had intestinal constipation at six months of age. In the bivariate analyzes, there was statistical significance for the liquidized food variable (p = 0.00) and after multivariate analysis it was verified that these foods were a risk factor for intestinal constipation RP = 1.50 (95% CI: 1.07 -2.11, p = 0.00). According to the kappa index, the agreement between the maternal impression that the child was evacuating every day was considered moderate (kappa = 0.55); (Kappa = 0, 18) and the stool appearance was substantial (kappa = 0.67). This study found prevalence of functional constipation in children at six months of age, similar to other studies developed in Brazil and the world, based on the maternal report. It is noteworthy that children who consumed liquefied foods were more likely to develop intestinal constipation. Regarding the reliability of the maternal impression, it was concluded that the characteristics of greater agreement corresponded to the appearance of hardened stools and to the daily frequency of bowel movements, emphasizing that the maternal report on the attached intestine can be a good indicator to recognize cases of intestinal constipation Six months of age. This project was approved by the Research Ethics Committee - CEP / UEFS - Protocol 077/2006 and the Higher Council for Teaching, Research and Extension - CONSEPE / UEFS - Protocol 154/2007, CAAE - 49106715.8.0000.0053.